2017
DOI: 10.1111/jfd.12629
|View full text |Cite
|
Sign up to set email alerts
|

Sickeningly Sweet: L‐rhamnose stimulates Flavobacterium columnare biofilm formation and virulence

Abstract: Flavobacterium columnare, the causative agent of columnaris disease, causes substantial mortality worldwide in numerous freshwater finfish species. Due to its global significance and impact on the aquaculture industry continual efforts to better understand basic mechanisms that contribute to disease are urgently needed. The current work sought to evaluate the effect of L-rhamnose on the growth characteristics of F. columnare. While we initially did not observe any key changes during the total growth of F. colu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 53 publications
3
14
0
Order By: Relevance
“…They concluded that the different carbohydrate receptors likely incorporated into the catfish mucus acted as bacterial chemoattractants. We reached a similar conclusion after demonstrating that in vitro biofilm formation was enhanced when stimulated with the carbohydrate, L‐rhamnose (Lange et al, ). We had also previously posited that the ability to form robust biofilms correlated with an ability to cause significant disease.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…They concluded that the different carbohydrate receptors likely incorporated into the catfish mucus acted as bacterial chemoattractants. We reached a similar conclusion after demonstrating that in vitro biofilm formation was enhanced when stimulated with the carbohydrate, L‐rhamnose (Lange et al, ). We had also previously posited that the ability to form robust biofilms correlated with an ability to cause significant disease.…”
Section: Discussionsupporting
confidence: 71%
“…However, when we examined the effect of catfish mucus on biofilm formation, it was shown that mucus alone was unable to drive the development of in vitro biofilms. Therefore, similar to a previous conclusion when evaluating the carbohydrate L‐rhamnose, fish mucus does not appear to be used solely as a nutrition source in the development of biofilms (Lange et al, ). Another possibility is that very little biofilm growth was observed in “mucus alone” due to limited nutritive iron availability in the mucus fractions (Hunter et al, ).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Biofilm formation could enhance the resistance to antibiotics (Khandekar et al., ; Yatip, Teja, Flegel, & Soowannayan, ) and host immune killing (Abdallah, Mahmoud, & Abdel‐Rahim, ; Chenia & Duma, ; Lange et al., ), while biofilm formation of Vibrio depends on complex regulatory processes (Cai et al., ). rpoS is involved in biofilm production in several bacteria, such as E. coli , Pseudomonas aeruginosa and Edwardsiella tarda (Xiao et al., ), although no such research about V. alginolyticus has yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Limited research has examined the terminal carbohydrate composition of fish mucus even though pathogen contact, and adhesion is often mediated by bacterial lectin receptors and/or host lectin receptors that bind to the sugars expressed by pathogens and/or at mucosal surfaces (Beck et al., ; Lange et al., ; Tse & Chadlee, ). All lectins tested bound to the mucus of channel and hybrid catfish albeit some with greater affinity that included Concavalia ensiformis lectin (conA), Lycopersicon esculentum lectin (LEA) and Triticum vulgaris lectin (WGA) in the greatest abundance (Figure ).…”
Section: Discussionmentioning
confidence: 99%